Development of a P2X1‐purinoceptor mediated contractile response in the aged mouse prostate gland through slowing down of ATP breakdown. Issue 3 (19th November 2013) - White, Carl W.; Short, Jennifer L.; Evans, Richard J.; Ventura, Sabatino
<x xml:space="preserve">Abstract</x> Aims An age‐related increase in prostatic smooth muscle tone is partly responsible for the lower urinary tract symptoms associated with benign prostatic hyperplasia (BPH). Changes in the effectors of prostatic smooth muscle contraction with age may play a role in the development of these symptoms. Using a mouse model of prostate contractility, this study investigated the effect of age on the different components of contractility in the prostate gland. Methods The isometric force developed in response to electrical field stimulation or exogenously applied agonists by mouse prostates mounted in organ baths, was evaluated to determine the effect of age on contractile mechanisms. Changes with age in the rate of ATP breakdown and levels of the P2rx1 gene and P2X1–purinoceptor expression in mouse prostate were measured by a modified luciferin–luciferase assay, RT‐PCR and western blot, respectively. Results Nerve mediated contractile responses containing a component elicited by P2X1‐purinoceptors were observed in prostates taken from aged mice, but not in prostates taken from young adult mice. Furthermore, the potency of the endogenous purinoceptor agonist ATP was 50‐fold greater in aged mice, whereas the potency of its stable analogue α, β‐metATP was unchanged. An age‐related decrease in ATP metabolism was also observed. Conclusions With age, a purinergic contractile response to nerve stimulation develops in the mouse prostate gland due to a decrease in the rate of ATP breakdown. This may contribute to the increase in muscular tone observed in BPH and suggests that P2X1‐purinoceptors are an additional target for the treatment of BPH. Neurourol. Urodynam. 34:292–298, 2015. © 2013 Wiley Periodicals, Inc.